MTPA Control Using Predictive P&O Method for Dual Parallel Surface-Mounted Permanent Magnet Synchronous Motor Drives Fed by a Single Inverter - Kim, Jae Seong; Lee, Kyo Beum (Conference Proceedings - IEEE Applied Power Electronics Conference and Exposition - APEC, 2025)
This paper presents maximum torque per ampere (MTPA) control using predictive perturbation and observation (P&O) method for dual parallel surface-mounted permanent magnet synchronous motor (SPMSM) drives fed by a single inverter. This control method adaptively adjusts the d-axis current that minimizes copper losses based on the predicted model of the electrical characteristics of the single inverter dual parallel (SIDP) SPMSM drive system. This optimized d-axis current is varied in real-time to enhance the efficiency of the SIDP SPMSM drive system. The proposed method ensures that the two motors operate at synchronized speeds while the SIDP SPMSM drive system satisfies the MTPA conditions. The validity of the proposed strategy for MTPA control in the SIDP SPMSM drive system is verified by simulations using PSIM software.
Keywords: Maximum Torque per Ampere; Maximum torque per ampere controls; Multi motors; Optimal efficiency; Optimal efficiency drive; Permanent magnet synchronous motor drive system; PMSM; Single inverter multi-motor; Single inverters; Surface mounted permanent magnet synchronous motor; Maximum torque per ampere; optimal efficiency drive; PMSM; single inverter multi-motor